Peran Perpustakaan Sekolah dalam Menumbuhkan Minat Baca Siswa SD Negeri 5 Kutosari - Primadani, Ariani Pradipta; Rifauddin, Machsun (Universitas Terbuka, 2024)
Abstrak Minat baca anak pada jaman sekarang sangatlah memprihatinkan. Rendahnya minat baca siswa SD Negeri 5 Kutosari dipengaruhi oleh beberapa faktor diantaranya kurang menariknya bahan pustaka serta kurangnya koleksi yang dimiliki Perpustakaan SD Negeri 5 Kutosari. Selain itu belum semua guru mengupayakan siswa-siswinya untuk mengunjungi perpustakaan dengan kegiatan membaca buku disaat jam kosong dan kurangnya waktu untuk mengunjungi perpustakaan. Dengan adanya program yang dilakukan perpustakaan, hasil penelitian ini dirasa cukup berhasil dalam menumbuhkan minat baca siswa di SD Negeri 5 Kutosari. Dalam penelitian ini, saya sebagai penulis menggunakan metode kualitatif dan pengumpulan data serta wawancara. Hal tersebut dilakukan dengan tujuan untuk menganalisis pengoptimalan peran perpustakaan dalam menumbuhkan minat membaca siswa SD Negeri 5 Kutosari. Maka, dengan adanya perpustakaan sekolah diharapkan mampu meningkatkan minat membaca siswa dengan lebih efektif dan efisien. Serta harapan untuk kedepannya dapat melahirkan generasi yang cerdas, kompeten, dan berkualitas. Akan tetapi masih ada kendala dalam mengoptimalkan peran perpustakaan yaitu kendala dana atau anggaran untuk pembelian buku, ruangan yang belum standar, dan dekorasi perpustakaan yang perlu diperbaharui. Kata kunci:Minat Baca, Peran Perpustakaan, Program, Perpustakaan Sekolah Abstract It is a matter of concern that the reading habits of children in the present era are not as encouraging as they should be. The low level of interest in reading among students at SD Negeri 5 Kutosari is influenced by a number of factors, including the lack of interest in the available reading materials and the limited number of books in the SD Negeri 5 Kutosari library. Furthermore, not all teachers encourage their students to visit the library during free periods, and there is insufficient time for students to visit the library. The implementation of the aforementioned programme has yielded considerable success in fostering a reading habit among students at SD Negeri 5 Kutosari. In this study, the researcher employed qualitative methods for data collection and interviews. The objective of this study was to analyse the optimal utilisation of the school library in fostering reading engagement among students at SD Negeri 5 Kutosari. It is therefore anticipated that the establishment of a school library will result in an increase in the effectiveness and efficiency with which students are encouraged to read. Furthermore, it is hoped that the programme will result in the emergence of a generation of intelligent, competent, and high quality individuals. Nevertheless, there are still obstacles to be overcome in order to optimize the role of the library. These include financial constraints, in the form of a lack of funds for the purchase of books, inadequate facilities, and a need to update the decor. Keywords: Reading Interest, Library Role, Programs, Libraries